An experimental work on the effect of the radius of rotation on the performance of revolving heat pipe (RVHP). (August 2017) - Hassan, Hamdy; Harmand, Souad
Highlights: Effect of rotational velocity and radius of rotation on the performance of RVHP is studied experimental. Temperature of RVHP decreases with increases rotational velocity and radius of rotation. Nusselt number of the base of RVHP increases with increase rotational Reynolds number. Radius of rotation hasn't sensible effect on the Nusselt number of RVHP for high input power. Abstract: Rotating heat pipe uses centrifugal acceleration to transfer condensed liquid from the condenser to evaporator. Revolving heat pipe (RVHP) is a rotating heat pipe but its axis of rotation is parallel to and offset from its central axis. This paper presents an experimental work on the effect of eccentric rotating of revolving heat pipe on its performance. RVHP used in our work consists of an evaporator region, an adiabatic region, and a condenser region. It is heated by constant heat flux at the evaporator outer surface and it is cooled by annual fins at the condenser outer surface. The experimental work is carried out at different rotational velocities, different radiuses of rotation, and different input powers to the heat pipe. The results show that the temperature of the RVHP increases with decreasing radius of rotation, and rotational velocity and with increasing input power. They also show that, at high rotational velocity, the radius of rotation and rotational velocity haven't a significant effect on the heat pipe temperature. At high rotational velocity, the thermal resistance of the RVHP decreases with increasing the rotational velocity. The radius of rotation has not sensible effect on the maximum Nusselt number of the RVHP of the studied cases at high input power. Increasing Reynolds number increases the Nusselt number on the surface of the heat pipe.